O papel dos pequenos mamíferos não-voadores na dispersão desementes em áreas protegidas: o potencial para a recuperação de áreas degradadas - Christiane Marta Genrich (2014)
The presence of natural environments helps ensuring availability of ecosystem services such as seed dispersal. Mutualistic interactions of seed dispersal by frugivores is important for the regeneration but the role of marsupials and rodents as seed dispersers is underestimated, though many species include fruits on their diets. The present study aimed to analyze the network of mutualistic interactions between plants and frugivores evaluating the role of small mammals as seed dispersers of pioneer plants and as potential providers of ecosystem services in the restoration of degraded mine-areas. The non-volant small mammals were sampled in three protected areas in the metropolitan region of Belo Horizonte, their scats were collected and seeds viability after gut passage was assessed to safely determine mutualism. The community of small terrestrial mammals and their food-plants in the study area were analyzed by means of a complex interaction network. Of the 17 species of small mammals recorded the species with viable seeds in scats were Didelphis albiventris, Didelphis aurita, Monodelphis domestica, Philander frenatus, Cerradomys scotti, Cerradomys subflavus, Necromys lasiurus and Oligoryzomys sp. Most of the seeds belonged to pioneer plants in the families Melastomataceae, Rosaceae, Rubiaceae, Solanaceae and Urticaceae. Rodents were as important dispersers as marsupials and the percentage of viable seeds species in their scats was larger than that for marsupials, a result not observed in other studies. The two species of rodents N. lasiurus and C. subflavus showed diet overlapping. The dietary pattern found in this study demonstrates a complementary role in seed dispersal between marsupials and rodents. Feeding on the same species of fruit may increase chance of species dispersion, while feeding on a variety of fruits can increase diversity of plants being dispersed. Both cases can be important in restoring vegetation. This study has an unprecedented character, being the first to introduce the complex mutualism interactions between rodents and marsupials and plants. The results of interactions between small mammals and viability of dispersed seeds suggest that the classification of animals as the dispersion of seeds should obey a continuous between animals unable to disperse viable seeds and those effective dispersers of large numbers of viable seeds of pioneer plants.